Colonization and maturation of the foal fecal microbiota from birth through weaning and the effect of weaning method - Jacquay, Erica (Kansas State University, 2017)
The objectives of these studies were to (1) characterize mare milk and fecal bacteria, and foal fecal microbiota from birth to 4 mo and (2) determine the effect of weaning and weaning method on foal fecal bacterial composition. Next generation sequencing of the V4 region of the bacterial 16S rRNA gene was performed using the Illumina Miseq according to Earth Microbiome Project protocols and sequencing data was analyzed using QIIME. In experiment 1, mare milk, mare fecal, and foal fecal samples were collected from 9 mare and foal pairs at birth (d 0), d 2, 7, and 1, 2, 3 and 4 mo. In experiment 2, 9 foals were separated into 2 treatments: abrupt (n = 5) and gradual (n = 4) weaning methods. Fecal samples were collected the day before weaning (d-1), the day of weaning (d 0) and post-weaning on d 1, 2, 3, 4, and 7. Blood was collected for analysis of cortisol concentration at 0800 h on d -1, 1, 2, and at 0800 h and 1100 h on d 0 and 4. Heart rate was recorded in 10 min intervals on the day of weaning starting 1 h before weaning to 2 h post-weaning, and again for 1 h starting 24 h after weaning. Results from experiment 1 showed newborn foal meconium and mare milk were similar in species diversity and composition; however, large shifts in composition and increases in foal fecal bacterial diversity occurred within the first week. By 1 mo, foal fecal bacterial composition did not differ in composition from mare feces at the phylum level (P = 1.0). Firmicutes, Bacteriodetes, Verrucomicrobia, and Spirochaetes were the dominant phyla found in feces of foals 1 mo and older and adult mare feces. For experiment 2, there were no differences in species diversity (P > 0.05) or separations in bacterial community structure between weaning methods or before and after weaning. There were minor shifts in relative abundance of specific phyla and genera in response to weaning. Foals in the abrupt treatment group had increased cortisol concentrations on d 1 (P < 0.05) and increased heart rate for 50 min after weaning on d 0 (P < 0.05). The foal is born with fecal microbial communities similar to milk that rapidly change during the first week of life, reaching the same composition of its dam by the first month. The foal fecal microbiota matures prior to weaning, therefore weaning did not cause drastic changes in bacterial composition. Although acute stress was increased in abruptly weaned foals, stress associated with different weaning methods did not influence the fecal microbiota within the first week post-weaning.
Keywords: Foal; Fecal; Microbiota; Mare; Milk; Weaning